Ultrasonic inactivation of microorganisms: A compromise between lethal capacity and sensory quality of milk. (May 2015) - Marchesini, Giorgio; Fasolato, Luca; Novelli, Enrico; Balzan, Stefania; Contiero, Barbara; Montemurro, Filomena; Andrighetto, Igino; Segato, Severino
Abstract: The aim of this study was to evaluate eight ultrasound (US) different combinations of amplitude (70 and 100%) and duration (50, 100, 200 and 300 s) for their lethal capacity against Escherichia coli, Pseudomonas fluorescens, Staphylococcus aureus and Debaryomyces hansenii, the generation of volatile compounds (VC) and their impact on milk sensorial descriptors. The strongest treatment (100% × 300 s) led to a population reduction of 4.61, 2.75, 2.09 and 0.55 log for D. hansenii, P. fluorescens, E. coli and S. aureus, respectively, but caused milk sensorial deterioration. Four descriptors (metallic, burnt, rubbery and sharp) were correlated with treatment duration. Each of them, using stepwise regression analysis, was found to be associated with one VC (dodecanoic acid, R 2 = 0.90; octanoic acid, R 2 = 0.82; δ-dodecalactone, R 2 = 0.81 and decanoic acid methyl ester, R 2 = 0.78) that could be considered as a marker for milk sensorial deterioration caused by US. Industrial relevance: In this study it is stated in what conditions ultrasounds (US) could be used as effective sanitation procedure without the production of off-flavours and what is the inactivation capacity toward E. coli, P. fluorescens and D. hansenii in that conditions. Moreover, our results indicate possible markers of milk sensory degradation caused by US treatments. These markers (dodecanoic acid, octanoic acid, δ-dodecalactone and decanoic acid methyl ester) could be used to check milk sensory quality after US treatment instead of using expensive and time consuming sensory tests. Highlights: Ultrasound (US) duration affected E. coli and P. fluorescens, but not S. aureus . D. hansenii was affected after treatments longer than 100 s at 100% intensity. US duration significantly affected the milk flavour. Metallic, burnt, rubbery and sharp flavours were correlated with US duration. Four volatile compounds were found to be markers of milk sensorial deterioration.